Simplifying
10 + 20x + -10 = 15x + -5x + 90
Reorder the terms:
10 + -10 + 20x = 15x + -5x + 90
Combine like terms: 10 + -10 = 0
0 + 20x = 15x + -5x + 90
20x = 15x + -5x + 90
Reorder the terms:
20x = 90 + 15x + -5x
Combine like terms: 15x + -5x = 10x
20x = 90 + 10x
Solving
20x = 90 + 10x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-10x' to each side of the equation.
20x + -10x = 90 + 10x + -10x
Combine like terms: 20x + -10x = 10x
10x = 90 + 10x + -10x
Combine like terms: 10x + -10x = 0
10x = 90 + 0
10x = 90
Divide each side by '10'.
x = 9
Simplifying
x = 9